2020
DOI: 10.1530/joe-20-0072
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy, but not dietary octanoic acid supplementation, stimulates the ghrelin-pituitary growth hormone axis in mice

Abstract: Circulating growth hormone (GH) concentrations increase during pregnancy in mice and remain pituitary-derived. Whether abundance or activation of the GH secretagogue ghrelin increase during pregnancy, or in response to dietary octanoic acid supplementation, is unclear. We therefore measured circulating GH profiles in late pregnant C57BL/6J mice and in aged-matched non-pregnant females fed with standard laboratory chow supplemented with 5% octanoic or palmitic (control) acid (n = 4–13/group). Serum total and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…12 As mentioned above, abnormal angiogenesis and hypertension are the typical performance of PE, so we suspected that ghrelin may be related to PE. Previous study showed that ghrelin protein can be detected in trophoblast cells, 13 indicating that ghrelin may play an important physiological role in healthy pregnancy. Ghrelin levels increase in the first trimester, reach a peak in the second trimester, and drop to their lowest in the third trimester.…”
Section: Introductionmentioning
confidence: 98%
“…12 As mentioned above, abnormal angiogenesis and hypertension are the typical performance of PE, so we suspected that ghrelin may be related to PE. Previous study showed that ghrelin protein can be detected in trophoblast cells, 13 indicating that ghrelin may play an important physiological role in healthy pregnancy. Ghrelin levels increase in the first trimester, reach a peak in the second trimester, and drop to their lowest in the third trimester.…”
Section: Introductionmentioning
confidence: 98%
“…Its mRNA is detectable on embryonic day 12 and 17 [16], with a peak at day 16 and a decrease thereafter [40]. In detail, ghrelin is mainly expressed in the cytoplasm of labyrinth trophoblasts in rat placenta [40] as well as in the placenta of mice [41]. Noteworthy, under conditions of intra-uterine growth restriction in rats, placental ghrelin mRNA and peptide were elevated [42].…”
Section: Placentamentioning
confidence: 95%
“…In rodents, at mid-pregnancy, such as on day 10 and 15 of pregnancy, plasma ghrelin was decreased [12,41], while on day 20 [12] and day 23 [41] it was increased compared to non-pregnant rats [12]. Comparison of fasting plasma ghrelin concentrations throughout pregnancy showed a decrease with time, resulting in the lowest ghrelin level by day 18 of pregnancy in one study [73], while in nonfasted rats an increase of circulating ghrelin throughout pregnancy was observed [13]; in both investigations there was a normalization of ghrelin concentration at parturition [73].…”
Section: Pregnancy and Deliverymentioning
confidence: 99%
“…The role of maternal gut hormones in GI adaptations to normal pregnancy is underinvestigated, and few studies have explored the capacity of these hormones to alter GI mucosal structure and affect satiety (55, 56). Current evidence on plasma acyl‐ghrelin (the active form of ghrelin) concentrations during pregnancy is equivocal, with reports of an increase (57) or decrease (58) in women, an increase in rats (59), and a decrease in mice (60). Furthermore, the effects of ghrelin on food intake during pregnancy are mostly unknown.…”
Section: Changes In Food Intake Regulation During Pregnancymentioning
confidence: 99%
“…GH levels increase throughout human pregnancy, with pituitary‐derived GH predominant in early pregnancy, whereas the placental GH variant predominates from mid to late pregnancy (Figure 3, (93)). Rats and mice do not possess the placental variant, and instead, pituitary‐derived GH levels increase during pregnancy, likely in response to placental signals (60, 94). Systemic infusion of human placental GH into pregnant mice reduced maternal insulin sensitivity without affecting food intake or body weight (95).…”
Section: What Is Driving Increased Food Intake In Pregnancy?mentioning
confidence: 99%